Effect of Sargassum polycystum extract on liver and kidney of diabetic rats - Muhamad Firdaus; Anies Chamidah; Annafi Riski Nurcholis; Siti Yulaikah; Pangestuty Yeni Anggraeni; Widya Adi Suryanata; Denny Alghafihqi; Rendi Hardiansyah (Pharmaciana, 2017)
Hyperglycemia has been known able to incuce the free radical formation. The reactivity of free radical can affect the dysfunction and structural adjustment on liver and kidney of the diabetic. Polyphenol is bioactive that able to ameliorate the reactivity of free radical. This substance is also contained in brown seaweed.One of brown seaweeds that found on the Indonesia waters is Sargassum polycystum. The objective of this study was to evaluate the S. polycystum extract (SPE) to reduce the damage of the function and structure of liver and kidney in diabetic rats. SPE was obtained by drying, milling, extraction by methanol, concentrating, degassing by nitrogen gas, and finally freeze-drying, respectively. The male of rat strain Wistar was induced to diabetic by streptozotocin. This study was divided into four groups, i.e., normal, diabetic, diabetic + gliclazide and diabetic + SPE, respectively. The treatments of this experiment were executed for 45 days. The polyphenol content, malondialdehyde level, SGPT and SGOT levels, and creatinine levels were measured by the spectrophotometer, the blood glucose level was quantified by glucometer, and the insulin content was determined by ELISA method. The altering of the tissue structure was analyzed by staining method of hematoxylin and eosin. The result showed that the treatment of SPE on diabetic rats able to reduce the blood glucose level, malondialdehyde level of liver, and kidney,Â  SGPT and SGOT level of liver, creatinine level of blood, and increase of insulin level and improve the liver, and kidney tissue profiles, respectively. These results indicate that SPE can reduce the destruction of structure and function on liver and kidney of the diabetics.Â